Length-Weight Relationship and Condition Factors of Hotate Clams (Patinopecten yessoensis) Cultivated in Funka Bay, Japan at Different Stations - Fasya Pingka Diandari; Emyliana Listiowati; Rima Oktavia Kusuma (Journal Of Artha Biological Engineering, 2024)
Hotate clams (Patinopecten yessoensis) are a species of Bivalvia that is often found in the waters of Funka Bay, Hokkaido, Japan. The information regarding the relationship between length and weight and condition factors for hotate clams is important for knowing their growth patterns. This research aimed to examine the length-weight relationship and conditions of 56 Hotate clams collected in August of 2022 at two different locations. The relationship between length-weight and growth patterns shows that the range of b values at stations A and B is 2.45, and 1.86 in the waters of Funka Bay while the growth pattern in Funka Bay displays negative allometric growth with r values ranging from 0.90-0.92 (strong positive correlation). The condition factor values for Hotate clams at stations A and B are 5.45 and 1.28. There is a good welfare value for Hotate clams because the condition factor (Kn) is greater than one.